Interactions of Heavy Metals on Enzymes in Carbohydrate Metabolism: In silico study on glucokinase and pyruvate kinase - Akmal Rizky Harun; Siti Ratna Jinan F; Bambang Setiawan; Noer Komari (Universitas Muhammadiyah Yogyakarta, 2022)
Cadmium (Cd2+) and mercury (Hg2+) are heavy metals, which can cause chronic inflammation, oxidative stress, obesity, hyperglycemia, and diabetes. Exposure to heavy metals cadmium and mercury can interfere with glycolysis metabolic functions through the inactivation of two key enzymes: glucokinase (GK) and pyruvate kinase (PyK). However, pathomechanism is unknown. Based on the background, this research was conducted. Enzyme structures were obtained from the RCSB Protein Data Bank (http://www.rcsb.org) with the following codes, GK (GDP ID: 3IDH) and PyK (GDP ID: 4IP7). The interaction between Cd and Hg with this enzyme was used via the MIB site: Metal Ion Binding site prediction and docking server (http://bioinfo.cmu.edu.tw/MIB/). Next, the target protein's interaction between metal ions and amino acids was visualized on UCSF Chimera 1.15. Based on the research results, the metal ion bond of mercury was more reactive than cadmium based on the number of amino acid residues bound. The bond was stronger based on a lower distance with PyK and GK enzymes. Therefore, mercury and cadmium metal ions were considered to inhibit the glycolysis process by causing the inactivation of the two enzymes.